STRATEGI KOMUNIKASI SECTION CUSTOMER ENGINEERING PT NUSANTARA COMPNET INTEGRATOR DALAM MENINGKATKAN EFISIENSI PROJECT MAINTENANCE (STUDY CASE ANALISIS SECTION IT SUPPORT - Fathan Fajri Salim; Silviana Mayasari; Sari Ekowati Hadi (CV Edujavare Publishing, 2025)
The rapid development of information technology in the digital era has transformed operational and communication patterns within organizations, including in the field of information technology maintenance services. Project maintenance efficiency is a key factor for success, influenced by the effectiveness of internal communication. This study employed a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The informants consisted of one Customer Engineer as the key informant and one IT Support as the supporting informant. Data analysis was conducted interactively through the stages of data reduction, presentation, and verification. The findings emphasize the importance of strategic organizational communication as a supporting factor for project success in the information technology sector. The research results show that a well-structured and planned communication strategy covering situation analysis, setting communication objectives, formulating key messages, identifying target audiences, selecting appropriate media, and conducting evaluation and feedback significantly contributes to work efficiency. Such strategies enhance the speed of information delivery, accuracy of coordination, and overall project efficiency.